Limits on an exotic Higgs decay from a recast ATLAS four-lepton analysis - Junyi Cheng; Rabia Husain; Lingfeng Li; Matthew J. Strassler (Journal of High Energy Physics)
Abstract The ATLAS collaboration, using 139 fb−1 of 13 TeV collisions from the Large Hadron Collider, has placed limits on the decay of a Z boson to three dark photons. We reproduce the results of the ATLAS analysis, and then recast it as a limit on a exotic Higgs decay mode, in which the Higgs boson decays via a pair of intermediate (pseudo)scalars a to four dark photons V (or some other spin-one meson). Across the mass range for m a and m V , we find limits on the exotic Higgs branching fraction BR(H → aa → V V V V ) in the range of 4 × 10−5 to 1 × 10−4.